Upaya Melestarikan Jajanan Tradisonal di Pasar Setono Betek Kediri Melalui Desain Ulang Marketing Mix - Zulistiani Zulistiani; Sri Aliami; Basthoumi Muslih; Ema Nurzainul Hakimah; Restin Meilina; Samari Samari (Jurnal Abdimas Akademika, 2022)
In 2017 the Kediri City government carried out a repair and rearrangement project for the Setono Betek market. This project causes a decrease in sales for the Sotono Betek Market traders because the traders have difficulty finding buyers who are their customers. Traditional snack traders are among those affected by this government project. Here the traditional snack traders have to work hard again to find new buyers who are expected to become customers in the future. Therefore, the service team from Nusantara University PGRI Kediri, Faculty of Economics and Business, Management Study Program provided guidance and assistance to redesign the Marketing Mix to increase sales of traditional snacks in the form of new innovations in sales. These innovations are in the form of product innovation (shape, size and color), marketing distribution innovation, and promotion innovation. The target of the service program is the traditional snack traders at the Setono Betek market, Kediri City, who live in the Setono Pande village, Kediri City, which is the area where the market is located. The method used by this service team is in the form of direction, training, mentoring and evaluation. From the results of the community service team's evaluation that the participants of the traditional snack traders of the Setono Betek market in Kediri City who redesigned the Marketing Mix experienced an increase in sales. Keywords: Traditional Snacks, Marketing Mix